Decrease of Kidney Function in Manufacture Industry Workers in West Java in 2022 and the Relationship with Individual and Occupational Risk Factors - Ferdy Nurhadi; Aria Kekalih; Muhammad Ilyas; Dewi Soemarko; Iwan Sugiarta (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Background: The incidence of chronic kidney disease is increasing with a fairly high annual death rate which is a serious health problem in the world because it has increased incidence, has an impact on morbidity and mortality as well as a serious socio-economic world including in Indonesia with the majority of the working age population in the manufacturing industry. Therefor an early detection of decreased kidney function and factors that influence it become necessity. Methods: This research is analytical quantitative research with a cross-sectional design using secondary data of MCU in Occupational Health and Safety Service Company in 2022 with total 2,304 data. The data includes of eGFR as dependent variable and individual risk factors, history of illness risk factors, clinical risk factors and occupational risk factors as independent variable.Result: The results of the study suggest there was a decrease in kidney function (Glomerular Filtration Rate / GFR <90 ml/minute/1.73m2) of 33,8% of the total manufacturing industry workers in West Java in 2022. The decrease of eGFR is influenced by individual, clinical and occupational risk factors.Conclusion: The conclusion, risk factors that influence the incidence of decreased renal function in manufacture industry workers in West Java in 2022 are male, age over 40 years old, conditions of grade I and II hypertension, obesity and periodes of work of more than 19 years, with the most dominant influence factor is male gender.